A STUDY OF DIRECTIVE SPEECH ACTS AND PERSONAL DEVELOPMENT FACTORS OF CRUELLA IN THE SELF-TITLED MOVIE - Sujatna, Meita L.; Pradani, Tiara A.; Chairunnisa, Audry A.; Saputra, Dicky; Fadhillah, Muhammad F.; Puteri, Salsabilla F. (CENTRAL ASIA AND THE CAUCASUS, 2022)
The research is based on the analysis of the utterances of Cruella in the self-titled movie written by Dodie Smith and directed by Craig Gillespie. It focuses on the directive speech acts performed by the main character and their relationship with the portrayal of the main character's personality. It aims to 1) identify the directive speech acts performed and 2) to find the factors that affect the personality development of the main character. The qualitative descriptive method was applied to analyse the data and categorize it using models [1] and [2]. The results showed that the ‘asking’ category (24.7%) and individual as well as environmental factors were prevalent. It can be concluded that directive speech acts can mould the characteristics of a main character, and justify personality analysis. It is recommended that further analysis of the subject should focus on the directive speech acts categories and their syntactical patterns to strengthen the justification.